Understanding Household Food Security through Financial Literacy and Self-Control: Evidence from Millennial Families in Urban Indonesia - Annisa Paramaswary Aslam; Ayu Kartini Parawansa; Regina (Economics and Business Journal (ECBIS), 2026)
Household food security remains a critical challenge for many millennial families, particularly in urban areas where rising food prices, unstable household income, and changing consumption patterns increase financial vulnerability. While previous studies have primarily emphasized economic factors, limited attention has been given to the combined roles of financial literacy and self-control in strengthening household food security. This study aims to examine the effects of financial literacy and self-control on household food security among millennial families in Mattoangin Village, Makassar City. A quantitative research design was employed using a survey of 180 millennial households selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that financial literacy has a positive and significant effect on household food security by improving financial planning and resource allocation. Self-control also exerts a significant positive influence by promoting disciplined spending behavior and reducing impulsive consumption. Furthermore, financial literacy and self-control jointly explain a substantial proportion of household food security. These findings highlight that both financial knowledge and behavioral discipline are essential for enhancing household resilience. The study recommends strengthening community-based financial education and behavioral intervention programs to promote sustainable household food security among urban millennial families.